Who Benefits from Local Financing of Public Services? A Causal Analysis - Lastra Anadón, Carlos; E. Peterson, Paul (Annenberg Brown University, 2020)
The efficiency-equity trade-offs in public service delivery may be influenced by the dependency of local governments on their own resources rather than inter-governmental grants. School districts in the United States are expected both to produce human capital efficiently and to provide educational opportunity equally. To ascertain school district trade-offs, we estimate effects of revenue source on student performances in math and reading. Achievement is estimated from 225,000 observations weighted to be district representative. Estimates are made with OLS, geographic discontinuity models exploiting differences at state borders, and 2SLS models that use changes in housing prices as an instrument. For every 10 percent increase in local revenue share, achievement increases by a sizeable 0.02 to 0.06 standard deviations. Gains for students from low socio-economic backgrounds are about half those from higher ones. Both voice and exit channels moderate the efficiency-equity trade-off. Implications for federalism and state policy are discussed.
Keywords: College access; College aspirations; Socioeconomic gaps; College costs and returns; Information; 53 Ciencias Económicas::5301 Política fiscal y hacienda publica nacionales; ODS 8 - Trabajo decente y crecimiento económico